(Magic Dopant) Amphoteric Behavior of a Redox‐Active Transition Metal Ion in a Perovskite Lattice: New Insights on the Lattice Site Occupation of Manganese in SrTiO3. (5th October 2016) - Maier, Russell A.; Johnston‐Peck, Aaron C.; Donohue, Matthew P.
Abstract : It is demonstrated that a transition metal redox‐active ion can exhibit amphoteric dopant substitution in the SrTiO3 perovskite lattice. In stoichiometric SrTiO3, the manganese dopant is preferably accommodated through isovalent substitution as Mn 2+ on the strontium site and as Mn 4+ on the titanium site. Previous studies have suggested that either type of substitution is possible for compositions with tailored Sr/Ti stoichiometry. Using electron paramagnetic resonance (EPR) spectroscopy, the site occupancy of dilute concentrations of manganese is investigated in SrTiO3 as a function of the Sr/Ti ratio. The tuned Sr/Ti ratio can be used to manipulate the nature of the manganese substitution, and it is shown that Sr‐rich compositions (Sr/Ti > 1.001) processed in air result in B ‐site isovalent doping. For B ‐site substituted manganese ions, a new EPR signal for aliovalent Mn 2+ is observed in compositions annealed under reducing atmosphere. The concentration of oxygen vacancies observed with EPR is also shown to depend on the Sr/Ti stoichiometry. With improved control over the site of substitution and valence state, doping with a transition metal redox‐active ion may facilitate the ability to engineer new electronic functionality into the perovskite lattice. Abstract : A transition metal redox‐active amphoteric dopant is investigated in the perovskite lattice. Electron paramagnetic resonance is used to determine the site occupancy of manganese ions doped in dilute concentrations in the SrTiO3 host lattice as a function of Sr/Ti cation non‐stoichiometry.